POLICY AND LINGUISTIC CONSIDERATIONS IN THE PROPOSED RENAMING OF WEST JAVA PROVINCE TO TATAR SUNDA - Sarip, Sarip; Fitriana, Diana; Azhari, Aidul Fitriciada; Absori, Absori; Dewi, Elya Kusuma; Adiantika, Hanif Nurcholish; Nurkhaeriyah, Nurkhaeriyah (Universitas Lampung, 2024)
This legal study investigates the implications of the proposed renaming of West Java Province to Tatar Sunda Province, employing the approach of intuitive semantic dualism to address issues of language, territory, ethnicity, and national identity. The research draws on data from academic journals, books, media reports, and interviews, comparing secondary data with field opinions on the languages and bordering regions of the Sundanese dialect. The findings reveal that, although the Sundanese linguistic system was expected to play a crucial role in the renaming process and promote territorial unity, it falls short due to the inclusion of regions such as Banten, pre-independence Batavia, and bilingual border areas in the east and north. This geographic and linguistic complexity means that the name